EFL Instructors’ Micro-Scaffolding in Writing Classrooms: The Case of Wollega University, Ethiopia - Dinagde, Nesibu Gudina; Wakuma, Melaku (TELL - US JOURNAL, 2023)
The study aimed at measuring the extent to which EFL teachers provide assistance to their students in classroom interactions by writing lessons of Communicative English Language Skills II at the micro level of scaffolding. Case study design was used to achieve the objective of the study. Data was gathered from six English instructors of Wollega University who were selected purposively. The teachers were video recorded while teaching writing lessons. Then the data were transcribed into text. Next, interactional extracts were identified and coded for contingency using van de Poll's (2012) model of contingency shift framework (CSF) and the results were quantified by frequency and percentages. The finding indicated that the teachers began an interaction with high level of control in most interactions, which hinders them to identify their students’ actual knowledge level. Most of their interactions in the writing classroom became noncontingent and partially contingent. Dominantly, the study reviled that in longer interactions, which could help learners to construct knowledge, teachers were not able to adjust their interactional moves according to the students’ understanding level. Thus, it was concluded that EFL teachers were not properly scaffolding the development of students’ learning. This urges teachers to give attention to the concept of scaffolding in their teaching to provide proper assistance for their learners in classroom interactions.